A PRAGMATIC ANALYSIS ON UTTERANCES IN THE NOBLE QUR'AN IN CHAPTER AN-NISA' - INAWATI, NUR AMRI (2010)
The study aims at describing the type of sentences and to identify the intention of the utterances in English Translation of Qur'an Chapter An-Nisa. In the study , the writer use qualitative research as the type of study.To collect the data, the writer uses observation and documentation methods. The data are utterances which include pragmatic force in English Translation of the Noble Qur'an Chapter An-Nisa. The data sourse of the research is Al-Qur'an. This research grammatical structure and pragmatic approach as the tehnicque of analyzing data i.e. by indentifiying the type of sentence, and its intention. The results of the research show that: (1) the type of the sentence is divided into three types: declarative sentence, imperative sentence and interrogative sentence. The high percentage of type the sentence is declarative sentence. (2) the intention of the utterances in Noble Qur'an Chapter An-Nisa has function to order, to forbide, to promise, to infirm, to assert, to threat, to warn, to suggest, to command, to persuade, and to refuse.